2015
DOI: 10.5935/abc.20150012
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hemodynamic Profile, Physical Capacity and Quality of Life in Pulmonary Hypertension

Abstract: BackgroundNo studies have described and evaluated the association between hemodynamics, physical limitations and quality of life in patients with pulmonary hypertension (PH) without concomitant cardiovascular or respiratory disease.ObjectiveTo describe the hemodynamic profile, quality of life and physical capacity of patients with PH from groups I and IV and to study the association between these outcomes.MethodsCross-sectional study of patients with PH from clinical groups I and IV and functional classes II a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
0
0
1
Order By: Relevance
“…In this study, the mean walking distance in the 6MWT was 451.5 ± 96.4 m, which is slightly higher than that found in a Brazilian registry (398 ± 152 m) 22 and similar to another Brazilian study, which reported 463 ± 78 m. 23 The figures from these Brazilian studies are higher than those reported in other registries, such as the American registry with 374 ± 129 m 24 and the French registry with 329 ± 109 m. 25 We observed a strong correlation between accelerometer data and 6MWT distance, a finding similar to other studies that also used an accelerometer to assess PA in patients with PAH. 3,19…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the mean walking distance in the 6MWT was 451.5 ± 96.4 m, which is slightly higher than that found in a Brazilian registry (398 ± 152 m) 22 and similar to another Brazilian study, which reported 463 ± 78 m. 23 The figures from these Brazilian studies are higher than those reported in other registries, such as the American registry with 374 ± 129 m 24 and the French registry with 329 ± 109 m. 25 We observed a strong correlation between accelerometer data and 6MWT distance, a finding similar to other studies that also used an accelerometer to assess PA in patients with PAH. 3,19…”
Section: Discussionsupporting
confidence: 84%
“…No acompanhamento de pacientes com hipertensão pulmonar, diversos aspectos são norteadores de decisões terapêuticas e determinantes do prognóstico (TORRES et al, 2015). Nos últimos anos, vários biomarcadores da HP foram investigados com o intuito de buscar um método eficiente e não invasivo de estratificação e monitorização (PLÁCIDO et al, 2017).…”
Section: Discussionunclassified